PENERAPAN PENDEKATAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ARTS, MATHEMATICS) TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS IV SD INPRES TAMARUNANG KABUPATEN GOWA - Wulandari, Ika; Nurlina; Hikmah Marisda, Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on the science learning outcomes of fourth-grade students at SD Inpres Tamarunang, Gowa Regency. This research is motivated by the low science learning outcomes of students due to the teacher-centered learning process, resulting in students being less active in learning. This study used a quantitative method with a pre-experimental design through a one-group pretest-posttest design. The study sample consisted of 27 fourth-grade students selected using a purposive sampling technique. Data collection techniques used tests, observation, and documentation. Data analysis was conducted using descriptive statistics and paired sample t-tests. The results showed that the average pre-test score of 49.63 was in the poor category, while the average post-test score was 84.26 in the good category. The results of the hypothesis test indicate that the implementation of the STEAM approach has an effect on the science learning outcomes of fourth-grade students at SD Inpres Tamarunang, Gowa Regency. The STEAM approach is able to create active, creative, and collaborative learning, thereby improving student learning outcomes.